(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Some patients still choose to have their teeth extracted, even though root canal therapy (RCT) has been shown to have high success rates. The decision is frequently impacted by low public awareness and the high costs of root canal therapy (RCTs), which serve as major obstacles to their wider implementation. Objectives: To identify the knowledge, attitude and factors that influence the patient’s decision to undergo endodontic treatment or implants. Methods: A cross-sectional study conducted between July 2024 and February 2025, based on selfstructured questionnaire, A sample recruiting strategy will rely on social media channels (e.g., Twitter, Snapchat, Instagram, WhatsApp, etc.) to source people from across Saudi Arabia (aged between 18 and 50). The sample size was determined using a Rao soft sample size calculator. Keeping an indicator percentage of 0.50, margin of error of 5% and confidence interval of 95%, the calculated sample size was 384. Results: In 529 participants, 65.2% did not have sufficient information about RCT, although 53.9% recognized its indications. About half of the decisions were motivated by financial concerns, which 82.4% chose RCT over extraction. 72.4% favored implants for tooth replacement, but only 15.9% said they knew implants “very well.” In cases of 42.9%, attitudes towards RCT were moderate, and in 45.7% its were positive. More importantly, income influenced knowledge levels, and age, and education responses to both treatments. Conclusion: Although RCT was the strongest preference for preserving natural teeth, many participants were concerned with pain, the cost of treatment, and the surgical procedures accompanying dental implants. Finding that economic factors were an important barrier to dental care access, there is a clear need for better communication and educational initiatives by the dental profession.